Treatment outcomes of statin dose optimization strategies in managing statin-associated muscle symptoms in a tertiary care hospitals: a retrospective cohort study - De Lena, Baroness Maria S.; Lim, Siegfried Kayne L.
Although the use of statins is prominent, current international and local guidelines have varying recommendations in the management strategies for statin-associated muscle symptoms (SAMS).